The implementation of Software as a Service (SaaS) in the monitoring system of students’ score at State Polytechnic of Lampung based on cloud computing - Dewi Kania Widyawati; Zuriati Zuriati (Jurnal Ilmiah ESAI, 2015)
Lampung State Polytechnic is one of the Indonesian universities with a vision to be the best 5 of vocational campus in Indonesia in 2020. To achieve the vision, this campus needs the development in many aspects to improve the quality of the graduates to compete with other college graduates in Indonesia. One of the efforts to improve the quality of graduates is by increasing the competence of the student. To face these challenges, this campus must also prepare programs to monitor the competence scores of each student. Therefore, an application that is capable of monitoring the scores in detail is needed to facilitate the students, lecturers, students advisors’ and parents to see the development of the scores any time. The technology developed for this application uses cloud computing. The technology enable the user to access the information via the internet without having to know the technology infrastructure that helps in the process of accessing the data. The service model used in this system is software as service with system development method using Rapid Application Development (RAD). The database design uses normalization techniques and tested through black box testing method.Keywords: cloud computing, software as service, Rapid Application Development, Normalization Techniques, black box testing